Emotion awareness and cognitive behavioural therapy in young people with autism spectrum disorder. (October 2018) - Roberts-Collins, Cara; Mahoney-Davies, Gerwyn; Russell, Ailsa; Booth, Anne; Loades, Maria
Young people with autism spectrum disorder experience high levels of emotional problems, including anxiety and depression. Adapted cognitive behavioural therapy is recommended for such difficulties. However, no evidence suggests whether emotion awareness is important in treatment outcome for young people on the autism spectrum. This study aimed to investigate the potential differences in emotion awareness between (1) young people on the autism spectrum and typically developing youth and (2) young people on the autism spectrum with and without experience of cognitive behavioural therapy. Three groups (aged 11–20 years) participated: (1) typically developing young people ( n = 56); (2) young people on the autism spectrum with no experience of cognitive behavioural therapy ( n = 23); and (3) young people on the autism spectrum who had attended cognitive behavioural therapy ( n = 33). All participants completed the Emotion Awareness Questionnaire–30 item version. Young people on the autism spectrum differed significantly from typically developing young people on the emotional awareness measure. Young people on the autism spectrum who had attended cognitive behavioural therapy scored significantly lower on the Differentiating Emotions subscale, and significantly higher on the Attending to Others' Emotions subscale, compared to young people on the autism spectrum who had not attended cognitive behavioural therapy. This study highlights the importance of psycho-educational components of cognitive behavioural therapy when adapting for young people on the autism spectrum.